Wireless Pressure Measurement and Power Generation Using Sensor - Sakthivel, J.; Jamuna, V. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
This paper has implemented and designed for measurement of pressure using wireless and applied it for our day-to-day power requirements. The pressure acts between the skin surface and its supporting surface that humans experience during daily activities. Here, we prefer sensors to measure the pressure, voltage and angle. Piezoelectric sensors are used for measure the pressure & voltage through LCD. Micro-Electro Mechanical Sensor (MEMS) is used to measure the speed from the 3D angle values. The Controller is developed to interface the Micro-electromechanical (MEMS) sensors and piezoelectric sensors that have been designed for analysis the pressure and get power during the body movement. By using the zigbee module, the analyzed pressure is transmitted and stored in the PC. The great advantage of this project is that it doesn’t require any external power supply. Using the DC-DC booster it can increase the generated voltage and stored in battery. It provides power supply for this device and some electronic applications. Such device provides low power consumption, convenient and comfortable testing system.